Dual mechanical impact of β-escin on model lipid membranes - Moleiro, Lara H.; Martín-Romero, María T.; Herráez-Aguilar, Diego; Santiago, José A.; Caselli, Niccolò; Dargel, Carina; Geisler, Ramsia; Hellweg, Thomas; Monroy, Francisco (Frontiers in Soft Matter, 2023)
Understanding the mechanical behavior of biological membranes is of paramount importance in cell biophysics and in developing new biomaterials for medicine. In this study, we delve into the mechanical impact of β-aescin, commonly referred to as escin, a naturally occurring biosurfactant derived from the seeds of the horse chestnut tree. To examine the modulable interaction between escin and DMPC, an archetypical fluid phospholipid, and an essential constituent of the cellular fluid membrane mosaic, we have used artificial models based on the liquid-crystal structure, for instance, bilayer vesicles and Langmuir monolayers. We have focused on energetic and kinetic aspects of escin insertion, when either transversally adsorbed or longitudinally integrated within these model membranes. By employing surface microscopies of epifluorescence and Brewster angle reflectivity, we have elucidated the structural phase behavior of the hybrid escin / phospholipid membranes, which exhibit dual mechanical properties characterized by both high rigidity and reduced fluidity. Notably, at low temperatures, we observe a soft glassy rheological behavior reminiscent of liquid-crystalline ordered phases, which turns into a fluidlike viscoelasticity resembling more disordered phases at physiological temperatures. The hybrid membranes behave in one way and another as both driven by an adsorption potential well imposed by escin cohesivity. These intriguing findings are discussed from a physicochemical perspective, highlighting their potential for future pharmacological designs and biomedical applications that exploit the dual mechanical impact of escin on biological membranes.